Development Of Literary Text Teaching Materials Based On Local Wisdom Culture Of North Sumatra - Syamsul Arif; Rosmaini Rosmaini; Lasenna Siallagan (Universitas Negeri Medan, 2023)
This study aimed to develop teaching materials for literary texts based on local wisdom culture of North Sumatera at Grade VII semester 2 and the digitalization of the learning. The literary teaching materials developed were folk poetry, fable, and fictional texts. This study used the Research & Development method referring to the 4-D model developed by Thigaranjan et al. This model consists of four development steps such as define, design, develop, and the disseminate. The data in this study was analysed by using descriptive qualitative analysis. The validation on the teaching materials developed was carried out by 3 experts, namely material expert, language expert, and media experts. Furthermore, the teaching materials developed was tested on preliminary field and main field testing for Junior High Schools (SMP) relevant with the model of research method used. The study results showed that the teaching materials got excellent qualification in content validation (91.06%), excellent qualification in language validation (90%), excellent qualification on media expert validation (89.76%), excellent qualification on learning practitioner validation (95%), and excellent qualification on student response trials (88.98%). Thus, from the results of the research conducted, it can be concluded that the teaching material developed is